2015
DOI: 10.1159/000371544
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates the Expression of Small-Conductance Ca<sup>2+</sup>-Activated K<sup>+</sup> Channels in Colonic Smooth Muscle Cells

Abstract: Aim: This study aimed to determine the effects of small-conductance Ca2+-activated K+ (SK) channels in colonic relaxation and the regulation of SK channels by estrogen. Methods: The contractile activity of muscle strips from male rats was estimated, and drugs including vehicle (DMSO), 17β-estradiol (E2), or apamin (SK blocker) were added, respectively. In a further experiment, muscle strips were preincubated with apamin before exposure to E2. The levels of the SK2 and SK3 protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
2
10
0
1
Order By: Relevance
“…This finding was supported by Hogan et al, who found that EST decreased human colonic smooth muscle contractility [18]. Our results were also in agreement with Tang et al, [29] who showed similar results in colonic circular muscle of rats. Also, EST has been demonstrated to inhibit smooth muscle contractility in other tissues such as the gall bladder [30] esophagus [31] and detrusor [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…This finding was supported by Hogan et al, who found that EST decreased human colonic smooth muscle contractility [18]. Our results were also in agreement with Tang et al, [29] who showed similar results in colonic circular muscle of rats. Also, EST has been demonstrated to inhibit smooth muscle contractility in other tissues such as the gall bladder [30] esophagus [31] and detrusor [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…In an in vitro study performed by Hogan et al EST has been shown to decrease human colonic smooth muscle contractility, 33 while another study showed similar results in colonic circular muscle of rats. 45 These findings are consistent with the results obtained in our in vitro study with rats where EST inhibited the SCCA. However, EST has been demonstrated to inhibit smooth muscle contractility in other tissues, such as the gall bladder, 46 esophagus, 47 detrusor, 48,49 aorta, 50 coronary arteries 51 and the carotid artery.…”
Section: The Acute Influence Of Female Gonadal Hormones On Scca and Osupporting
confidence: 92%
“…The inhibitory effect of the acute administration of female gonadal hormones on gastrointestinal smooth muscle contractility that contrasts with physiological chronic action has been investigated in several previous studies. In an in vitro study performed by Hogan et al EST has been shown to decrease human colonic smooth muscle contractility, while another study showed similar results in colonic circular muscle of rats . These findings are consistent with the results obtained in our in vitro study with rats where EST inhibited the SCCA.…”
Section: Discussionmentioning
confidence: 99%
“…SK and IK channels are two distinct types of voltage-independent K Ca channels; these channels exhibit a close association between their calcium sensitivity and calmodulin [42]. In contrast to intestinal smooth muscle, little evidence is available suggesting a functional role for SK channels in vascular smooth muscle cells, although an unidentified apamin (a specific blocker of SK channel channels)-sensitive and voltage-dependent conductance has been reported [43]. In healthy and freshly isolated vascular smooth muscle cells, IK channels are expressed at very low levels.…”
Section: Structures Of Sk and Ik Channelmentioning
confidence: 99%